Risk disclosures by South African listed companies post-King III. Issue 1 (2nd January 2016) - Raemaekers, Kim; Maroun, Warren; Padia, Nirupa
Abstract : The introduction of principles on the governance of risk in the King Code on Corporate Governance (King III), coupled with the drive for more integrated models of reporting, has highlighted the need for effective communication of risks and risk-management strategies to stakeholders. To date, however, there has been little research on trends in risk disclosure practices by large firms listed on the Johannesburg Stock Exchange (JSE). As such, this research adds to the body of integrated reporting literature by examining changes in the extent of risk disclosures by these companies from 2010 to 2012. The research finds that, although there has been an increase in disclosure over this period, there is a possibility of reporting on the governance of risk being a compliance-based exercise rather than an example of effective stakeholder communication.